Porcine circovirus‐2 in Africa: Identification of continent‐specific clusters and evidence of independent viral introductions from Europe, North America and Asia. Issue 4 (3rd December 2021) - Franzo, Giovanni; Settypalli, Tirumala B.K.; Agusi, Ebere Roseann; Meseko, Clement; Minoungou, Germaine; Ouoba, Bruno Lalidia; Habibata, Zerbo Lamouni; Wade, Abel; de Barros, José Luís; Tshilenge, Curé Georges; Gelaye, Esayas; Yami, Martha; et al.
Abstract: Porcine circovirus‐2 (PCV‐2) is associated with several disease syndromes in domestic pigs that have a significant impact on global pig production and health. Currently, little is known about the status of PCV‐2 in Africa. In this study, a total of 408 archived DNA samples collected from pigs in Burkina Faso, Cameroon, Cape Verde, Ethiopia, the Democratic Republic of the Congo, Mozambique, Nigeria, Senegal, Tanzania and Zambia between 2000 and 2018 were screened by PCR for the presence of PCV‐2. Positive amplicons of the gene encoding the viral capsid protein (ORF2) were sequenced to determine the genotypes circulating in each country. Four of the nine currently known genotypes of PCV‐2 were identified (i.e. PCV‐2a, PCV‐2b, PCV‐2d and PCV‐2 g) with more than one genotype being identified in Burkina Faso, Ethiopia, Nigeria, Mozambique, Senegal and Zambia. Additionally, a phylogeographic analysis which included 38 additional ORF2 gene sequences of PCV‐2s previously identified in Mozambique, Namibia and South Africa from 2014 to 2016 and 2019 to 2020 and available in public databases, demonstrated the existence of several African‐specific clusters and estimated the approximate time of introduction of PCV‐2s into Africa from other continents. This is the first in‐depth study of PCV‐2 in Africa and it has important implications for pig production at both the small‐holder and commercial farm level on the continent.